Perspective of Law Enforcement Officials with the Emergence of the “No Viral, No Justice” Phenomenon - Brezillya Anggraini; Renita Tresna (Westscience Press, 2024)
The “no viral no justice” phenomenon in a social media-active society implies that justice is only obtained if a case or legal event goes viral first. Law enforcement should not depend on how much public attention is given to the case. This phenomenon arises because of the assumption that viral cases are handled more quickly than cases that are reported normally. The research method used is the normative juridical method with data collection techniques in the form of literature and literature studies. Data analysis is done descriptively and qualitatively. One of the main factors that slow down the handling of cases by law enforcement officials in Indonesia is their low quality, which has an impact on the lack of professionalism and moral ethics. Therefore, the “no viral no justice” phenomenon actually plays an important role in overseeing the professionalism of law enforcement agencies. However, from a telecommunications perspective, this phenomenon does not provide a guarantee of legal protection against the dissemination of personal information or a person's disgrace from an unclear source, which may violate Law No. 36/1999 on Telecommunications.